How the use of nitrogen fertiliser may switch plant suitability for aphids: the case of Miscanthus, a promising biomass crop, and the aphid pest Rhopalosiphum maidis. Issue 8 (3rd February 2017) - Bogaert, Florent; Chesnais, Quentin; Catterou, Manuella; Rambaud, Caroline; Doury, Géraldine; Ameline, Arnaud
Abstract: BACKGROUND: The use of nitrogen fertiliser in agrosystems can alter plant nitrogen and consequently improve nutrient availability for herbivores, potentially leading to better performance for herbivores and higher pest pressure in the field. We compared, in laboratory conditions, the effects of nitrogen fertilisation on a promising biomass crop, Miscanthus × giganteus, and its parents M. sinensis and M. sacchariflorus . The plant‐mediated effects were compared on the second trophic level, the green corn leaf aphid Rhopalosiphum maidis . RESULTS: Results showed that the biomass and leaf C:N ratio of M. sinensis plants treated with nitrogen fertiliser were significantly greater than those of non‐treated plants. As regards M. × giganteus and M. sacchariflorus, the only reported change was a significantly smaller leaf C:N ratio for treated M. sacchariflorus compared with non‐treated plants. Surprisingly, nitrogen fertilisation had opposite effects on plant–herbivore interactions. Following nitrogen treatments, M. sinensis was less suitable in terms of intrinsic rate of increase for R. maidis, the feeding behaviour of which was negatively affected, while M. sacchariflorus and M. × giganteus exhibited greater suitability in terms of aphid weight. CONCLUSION: Nitrogen fertilisation had contrasting effects on the three species of Miscanthus plants. These effects cascaded up to the second trophic level, R. maidis aphid pests, either through a modification of their weight or demographic parameters. The implications of these results were discussed in the context of agricultural sustainability and intensive production practices. © 2016 Society of Chemical Industry